Hepatic Stellate Cells Functional Heterogeneity in Liver Cancer - Sererols-Viñas, Laura; Garcia-Vicién, Gemma; Ruiz-Blázquez, Paloma; Lee, Ting-Fang; Lee, Youngmin A.; Gonzalez-Sanchez, Ester; Vaquero, Javier; Moles, Anna; Filliol, Aveline; Affò, Silvia (Seminars in Liver Disease, 2025)
Hepatic stellate cells (HSCs) are the liver's pericytes, and play key roles in liver homeostasis, regeneration, fibrosis, and cancer. Upon injury, HSCs activate and are the main origin of myofibroblasts and cancer-associated fibroblasts (CAFs) in liver fibrosis and cancer. Primary liver cancer has a grim prognosis, ranking as the third leading cause of cancer-related deaths worldwide, with hepatocellular carcinoma (HCC) being the predominant type, followed by intrahepatic cholangiocarcinoma (iCCA). Moreover, the liver hosts 35% of all metastatic lesions. The distinct spatial distribution and functional roles of HSCs across these malignancies represent a significant challenge for universal therapeutic strategies, requiring a nuanced and tailored understanding of their contributions. This review examines the heterogeneous roles of HSCs in liver cancer, focusing on their spatial localization, dynamic interactions within the tumor microenvironment (TME), and emerging therapeutic opportunities, including strategies to modulate their activity, and harness their potential as targets for antifibrotic and antitumor interventions.
Keywords: hepatic stellate cells; liver cancer; cancer-associated fibroblasts; tumor microenvironment